Prawo pacjenta do świadczeń zdrowotnych z zakresu lecznictwa uzdrowiskowego - Jachimowicz-Jankowska, Paulina (Wydawnictwo Naukowe UAM, 2020)
The right to use health services, including spa treatment, is one of the basic patient rights. The specificity of the issues undertaken stems from at least two sources. First of all, patients are a special category of people, because human health, as the highest value possessed by every human being, is subject to legal protection and requires their rights and freedoms are guaranteed. Secondly, spa treatment, which is an integral part of the health care system, corresponds to art. 68 of the Polish Constitution, assuming the fundamental principle according to which every citizen has the right to health care. On the other hand, this treatment means providing health services, which are conducted only in a separate area of the spa commune – a spa and in specially adapted medical entities – spa treatment centers. The study covers the concise genesis of patient rights and the notion of the patient in terms of doctrine and legislation. Moreover, it contains the basic concepts related to spas. Recognition of the health needs of society is associated with a presentation of the individual types of spa treatment centers and spa treatment facilities, as well as the necessary conditions that they should meet. Due to the existing different status of patients in spa treatment institutions, the analysis covers the basis for admission, for referring and qualifying patients to these centers, and also the rules for using services guaranteed in the field of spa treatment. The patient’s right to health services is also examined in the context of using these services. Despite the fact that patients’ interest in this form of treatment increases every year, as is shown by the available data, there are a number of legal and organizational problems related to access to treatment as part of spa services.
Keywords: patient and patient’s rights; health protection; health service; spa treatment; spa treatment center in a health resort